Pengaruh Social Support, Self Efficacy terhadap Kepuasan Hidup dan Adaptabilitas Karir pada Mahasiswa Tingkat Akhir - Dita Nurmala Dewi; Tirton Nefianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Final year students often experience difficulties in adapting to career and life demands, as well as maintaining their well-being. This study aims to examine the influence of social support and self-efficacy on life satisfaction and career adaptability among final-year students. Quantitative data were collected from 155 students in their final year of study and analyzed using Structural Equation Modelling (SEM). The results showed that social support did not affect the career adaptability of final-year students. Conversely, self-efficacy had a positive effect on career adaptability. Social support was found to have a positive impact on students' life satisfaction. Students who received social support from family, friends, and educational institutions tended to have higher levels of life satisfaction. Self-efficacy also positively affected life satisfaction, indicating that high self-confidence enhances individual well-being. However, life satisfaction did not significantly influence career adaptability, suggesting that other factors such as work experience and environmental support play a more significant role. This study has several limitations, including a limited sample size and potential respondent bias. Future research should involve larger and more diverse samples and employ a variety of data collection methods. Educational institutions are encouraged to develop programs that enhance self-efficacy and social support to help students reach their full potential in their careers and personal lives.